Novel tri-specific T-cell engager targeting IL-13Rα2 and EGFRvIII provides long-term survival in heterogeneous GBM challenge and promotes antitumor cytotoxicity with patient immune cells - David B Weiner; Donald O’Rourke; Kevin Liaw; Pratik S Bhojnagarwala; Devivasha Bordoloi; Daniel H Park; Nicholas J Tursi; Shushu Zhao; Zev A Binder (Journal for ImmunoTherapy of Cancer)
Background Glioblastoma multiforme (GBM) is known for its high antigenic heterogeneity, which undermines the effectiveness of monospecific immunotherapies. Multivalent immunotherapeutic strategies that target multiple tumor antigens simultaneously could enhance clinical outcomes by preventing antigen-driven tumor escape mechanisms.Methods We describe novel trivalent antibodies, DNA-encoded tri-specific T-cell engagers (DTriTEs), targeting two GBM antigens, epidermal growth factor receptor variant III (EGFRvIII) and IL-13Rα2, and engaging T cells through CD3. We engineered three DTriTE constructs, each with a unique arrangement of the antigen-binding fragments within a single-chain sequence. We assessed the binding efficiency and cytotoxic activity of these DTriTEs in vitro on target cells expressing relevant antigens. In vivo efficacy was tested in immunocompromised mice, including a longitudinal expression study post-administration and a survival analysis in an NOD scid gamma (NSG)-K mouse model under a heterogeneous tumor burden. RNA sequencing of DTriTE-activated T cells was employed to identify the molecular pathways influenced by the treatment. The antitumor cytotoxicity of patient-derived immune cells was evaluated following stimulation by DTriTE to assess its potential effectiveness in a clinical setting.Results All DTriTE constructs demonstrated strong binding to EGFRvIII and IL-13Rα2-expressing cells, induced significant T cell-mediated cytotoxicity, and enhanced cytokine production (interferon-γ, tumor necrosis factor (TNF)-α, and interleukin(IL)-2). The lead construct, DT2035, sustained expression for over 105 days in vivo and exhibited elimination of tumor burden in a heterogeneous intracranial GBM model, outperforming monospecific antibody controls. In extended survival studies using the NSG-K model, DT2035 achieved a 67% survival rate over 120 days. RNA sequencing of DTriTE-activated T cells showed that DT2035 enhances genes linked to cytotoxicity, proliferation, and immunomodulation, reflecting potent immune activation. Finally, DT2035 effectively induced target-specific cytotoxicity in post-treatment peripheral blood mononuclear cells from patients with GBM, highlighting its potential for clinical effectiveness.Conclusions DTriTEs exhibit potent anti-tumor effects and durable in vivo activity, offering promising therapeutic potential against GBM. These findings support further development of such multivalent therapeutic strategies to improve treatment outcomes in GBM and potentially other antigenically heterogeneous tumors. The opportunity to advance such important therapies either through biologic delivery or direct in vivo nucleic acid production is compelling.